ANALISA KINERJA WAKTU PELAKSANAAN PEMBANGUNAN GEDUNG DI SEKOLAH MENENGAH KEJURUAN NEGERI (SMKN) 1 PULO AMPEL SERANG - Siti Rosmawati; Telly Rosdiyani; Euis Amilia; Bambang Hariyanto (Universitas Medan Area, 2025)
The construction project of infrastructure building at State Vocational High School (SMKN) 1 Puloampel, Serang Regency, aims to provide better facilities to support the improvement of education quality. Although the project was well-planned, time and cost deviations occurred, affecting the project’s progress. This study aims to analyze the time and cost deviations using the Earned Value Analysis (EVA) method. The data used includes weekly data from week 1 to week 22, with a total project duration of 22 weeks. The results show that the project experienced delays in several weeks, specifically in weeks 1, 10, 11, 15, 16, 19, and 20, resulting in a total delay of 27 days. These time deviations led to a cost overrun of IDR 20,052,074.54. The causes of delay were mainly due to late site preparation, water and equipment needs, and delayed material deliveries. As a solution, it is recommended to add more labor, speed up material delivery, and revise the schedule to avoid further delays and cost overruns.